The Significance of Super Depo Sutorejo: Waste Management Project in Surabaya Municipality, Indonesia - Windi, Yohanes Kambaru; Wijayanti, Dyah; Wiyatno, Eko Rustamaji; Rahariyani, Loetfia Dwi (UI Scholars Hub, 2021)
The Super Depo Sutorejo Surabaya (SDSS) Project was created to separate household waste into fractions, but its separation effect is unknown. This study assessed the significance of the project in sorting general waste into biodegradable, non-biodegradable, and assorted. The t-test compared the means of general and biodegradable waste (normally distributed). The non-biodegradable and assorted waste were not significantly distributed; therefore, the Wilcoxon Signed Ranks Test was used to compare their medians against general waste. The multivariate analysis compared the significance level of each waste fraction. Each statistical analysis showed that the SDSS significantly sorts the general waste. The p-values were (0.000) <0.05 for each type of waste fraction. Furthermore, the multivariate analysis showed that all variables were similar, and p-values (0.00) <0.05. The biodegradable waste was the most significant fraction (M = 176,715.9; SD = 57,990.8), followed by the assorted (M = 171,412.5; SD = 94,631.3), and non-biodegradable (M = 35,243.8; SD = 17,290.7). The results showed that the SDSS significantly segregates general waste into biodegradable, non-biodegradable, and assorted, therefore hypothesis (H1) is accepted. This study recommends the Government of Surabaya to maintain and expand this waste management project throughout the city alongside the improvement of the community participation program.